Differences in physical demands between international and national female Rugby Sevens players - Portillo, L. J.; Suarez-Arrones, L.; Sanchez M.; Sanchez, F.; Garcia, J. M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In this study, the physiological demands of an international and national women`s rugby 7´s were investigated during competition. Obtaining measures of physiological demands between different level of performance in rugby 7´s female players during the competition match enabled us to determine how these athletes responded to a competition and if exists differences between physiological and movement patterns. METHODS: Variables were measured by means of GPS receivers and HR monitors. In order to determine whether there were physiological changes in these aspects, participants were tested during international and national tournament. The data used in the study was gathered from 20 players (10 international and 10 national players) during four matches in both levels of competition. RESULTS: The results of this study show that, during a Rugby 7`s match, there are differences in the physiological profile of international and national female rugby sevens players. Mean total distance (± SD) covered over the whole match by international players was 1642 ± 171.20 m. and national players was 1363,45 ± 221,87. The number of sprints during the match by international players was 6,18 ± 3,13 and national players was 1,97 ± 1,49. The distance of high-speed zone (> 20 km/h) was 62,01 ± 37,80 m. and 21,10 ± 24,50 m. The average speed obtained throughout the game was 6,06 ± 0,33 km/h and 5,29 ± 0.63.km/h .The international players spent at HR intensities (> 95%) expressed as percentage of HRmax, 26,55 ± 16,09% and national players was 13,28 ± 10,60%. In general, physical demands were significantly greater (p < 0.01-0.001) by international players. DISCUSSION: The results of this study are similar to those obtained by (Suárez -Arrones L. et al., 2011) in the physiological profile of international female rugby sevens player. The data of studies (Anita C. Sirotic et al., 2009; Cameron Brewer A et al., 2010; D. G. Higham et al., 2011) examine differences in physical performance betwen elite and smi-elite games findings significantly differences.Collectively, these findings provide important information that can be used in the training process for improve specific qualities of female rugby 7s.